Factors associated with families’ participation in urban solid waste separation in Texcoco, State of Mexico - Abelino-Torres, Gonzalo; Quispe-Limaylla, Anibal G.; Pérez Hernández, Luz María; Leos-Rodríguez, Juan Antonio; Carranza Díaz, Otoniel; Flores Sánchez, Diego (Acta Universitaria, 2019)
In Mexico, 5% of the urban solid waste (USW) is recycled. By reason of families’ participation, more than 60% of USW could be recovered. A personal interview survey was conducted among a random sampling of 397 heads of household in Texcoco, Mexico, which were selected from the National Geostatistical Framework. Factors associated with families’ participation in USW separation were identified through the Chi-Square Test. By using Cramer’s V, it was found that variables, which constitute cognitive dimension of environmental consciousness, are associated to USW separation with higher scores than the other variables. The Cochran-Mantel–Haenszel Test statistics revealed that when a person knows the environmental benefits of solid waste separation, his/her probability to separate his/her USW increases by more than four times when calculated by age, gender, and knowledge about the use of USW strata.